2019
DOI: 10.1016/j.atherosclerosis.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic calcification in major vessel beds in chronic obstructive pulmonary disease: The Rotterdam Study

Abstract: is related to calcifications in the extracranial arteries. • COPD may affect atherosclerosis in various vessel beds differently. • COPD is related to arterial calcification independent of smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, even after adjusting for extracranial carotid artery stenosis, we found a statistically significant association between COPD GOLD2-3 and cerebral blood flow. While previously not found to be more prevalent in subjects with COPD, 32 intracranial stenotic lesions may still mediate some of the effect of lowered cerebral blood flow in subjects with COPD GOLD2-4 due to shared underlying risk factors. Moreover, despite being associated with both cardiovascular disease and cerebral blood flow, ApoE status seemed not to be a confounder of the association between COPD and cerebral blood flow since it is not differential between participants with and without COPD.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Nevertheless, even after adjusting for extracranial carotid artery stenosis, we found a statistically significant association between COPD GOLD2-3 and cerebral blood flow. While previously not found to be more prevalent in subjects with COPD, 32 intracranial stenotic lesions may still mediate some of the effect of lowered cerebral blood flow in subjects with COPD GOLD2-4 due to shared underlying risk factors. Moreover, despite being associated with both cardiovascular disease and cerebral blood flow, ApoE status seemed not to be a confounder of the association between COPD and cerebral blood flow since it is not differential between participants with and without COPD.…”
Section: Discussionmentioning
confidence: 71%
“…Previously, we showed aggravated extracranial-but not intracranial-carotid artery calcifications in subjects with COPD. 32 Hence, large artery atherosclerosis of the extracranial carotid arteries presumably contributes to impaired cerebral blood flow in these subjects, through both flow reducing effects of artery stenosis and vasodilatation limiting effects of arterial stiffening. Nevertheless, even after adjusting for extracranial carotid artery stenosis, we found a statistically significant association between COPD GOLD2-3 and cerebral blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, calcification at extracranial and intracranial carotid arteries is more severe in women with arterial hypertension, whereas in men, the strongest association was found between arterial hypertension and vertebrobasilar arteries [ 19 ]. Another study from Rotterdam survey also showed that chronic obstructive pulmonary disease plays a clear central role as a risk factor for the presence of calcification at different sites (coronary, aortic arch, extra- and intra-cranial carotid artery) [ 20 ].…”
Section: Arterial Wall Remodeling During Agingmentioning
confidence: 99%
“…Abdominal aortic calcification (AAC), a complex and multifactorial process of mineral deposition in arterial wall [11][12][13], is a stable marker of atherosclerotic vascular disease. AAC has been shown to predict future CVD events, poor prognosis [14][15][16] and all-cause mortality [17].…”
Section: Introductionmentioning
confidence: 99%